2006
DOI: 10.1111/j.1349-7006.2006.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic or epigenetic silencing of low density lipoprotein receptor‐related protein 1B expression in oral squamous cell carcinoma

Abstract: Previously, we have reported frequent silencing of the expression of LRP1B by genetic and epigenetic mechanisms in esophageal squamous cell carcinoma. As the same events might be involved in the development/progression of OSCC, we examined intragenic homozygous deletions, expression levels, and methylation status in the CpG island of this gene. Homozygous deletion was detected in only 1 of 18 (5.6%) OSCC lines, whereas the expression of LRP1B mRNA was silenced in 8 of 17 (47.1%) OSCC lines without homozygous d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…LRP1B has been classified as a tumor suppressor gene and is frequently mutated in GBM (42)(43)(44)(45)(46)(47). We discovered a novel internal deletion of LRP1B in the U118 GBM cell line and four GBM samples.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…LRP1B has been classified as a tumor suppressor gene and is frequently mutated in GBM (42)(43)(44)(45)(46)(47). We discovered a novel internal deletion of LRP1B in the U118 GBM cell line and four GBM samples.…”
Section: Discussionmentioning
confidence: 90%
“…Other studies have suggested that LRP1B may be a tumor suppressor gene that is deleted or abnormal in several other tumor types, as well as GBM (42)(43)(44)(45)(46)(47). In addition, LRP1B is deleted or epigenetically silenced in oral urothelial, esophageal, and non-small-cell lung cancers; taken together, LRP1B behaves as a tumor suppressor gene that is frequently mutated in several solid tumors, including GBM (42)(43)(44)(45)(46)(47). Our data suggest that LRP1B acts as a tumor suppressor gene in glioma cells and is aberrant in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found homozygous deletions of LRP1B exons 1, 5, 7, and 10 in other cancers (Liu et al, 2000a;Sonoda et al, 2004;Nakagawa et al, 2006). To investigate whether homozygous deletion of these LRP1B exons is common in gastric cancer, we used quantitative real-time genomic PCR to detect homozygous deletions in proximal exons (1, 5, 7, and 10) and distal exons (85 and 88) in gastric cancer cell lines, normal stomach tissue and 74 paired tumor/ adjacent normal tissue.…”
Section: Lrp1b Hypermethylation and Deletion In Gastric Cancer Clinicmentioning
confidence: 97%
“…One of our candidate genes LRP1B, ranked number four among the 107 differential hypermethylated genes (P < 0.001, Supporting Information Fig. S1) has previously been shown to be genetically or epigenetically silenced in cancers (Sonoda et al, 2004;Nakagawa et al, 2006). To analyze whether LRP1B is indeed differentially methylated in gastric cancer, we performed LRP1B bisulfite sequencing using gastric cancer cell lines and normal stomach tissue.…”
Section: Hypermethylation Of Lrp1b In Gastric Cancer Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation